The Effect of Nutmeg Leaves Tannin (Myristica fragrans Houtt) as Protein Protecting Agents on In Vitro Nutrient Digestibility - Monica Canadianti; Lies Mira Yusiati; Chusnul Hanim; Budi Prasetyo Widyobroto; Andriyani Astuti (Buletin Peternakan, 2020)
This experiment was aimed to study the effect of nutmeg leaf tannin addition on in vitro nutrient digestibility. Treatments in this experiment consisted of: P0 (control without tannin), P1 (feed + 2% tannin) and P2 (feed + 4% tannin). Feed for fermentation substrate consisted of Pennisetum purpureum and soybean meal with ratio 60:40. Fermentation was carried out using Tilley and Terry two stages in vitro technique for 48 hours. Variables measured were the digestibility of dry matter, organic matter, and crude protein in the rumen as well as the total digestive tract digestibility based on in vitro technique. The data obtained were analyzed by One Way ANOVA, and followed by the Duncan Multiple Range Test (DMRT). The results showed that rumen dry matter digestibility was lower (P<0.05) in P1 and P2 (59.03±3.24 and 57.19±1.32) compared to P0 (70.77±1.05), but did not show a significant difference (P>0.05) in the total dry matter digestibility of P0, P1, and P2 (74.88±5.28, 67.70±3.21, and 64.83±4.96). Organic matter digestibility in the rumen was also lower (P<0.05) in P1 and P2 (55.55±6.29 and 55.76±6.88) compared to P0 (75.39±0.91), but did not show significant difference (P>0.05) in total organic matter digestibility from P0, P1, and P2 (64.69±6.44, 64.33±6.34, and 61.20±5.11). The digestibility of crude protein in the rumen at P1 and P2 (45.48±5.12 and 38.47±3.44) was also significantly lower (P<0.05) compared to P0 (60.93±9.72), whereas total digestibility did not show any significant difference (P>0.05). Addition of tannin leaf nutmeg 2% optimally reduced rumen dry matter and crude protein digestibility without causing excessive negative impact on results of in vitro digestibility, so it can be used as a protective agent protein feed.